Knowledge mapping of autophagy in osteoarthritis from 2004 to 2022: A bibliometric analysis - Liao, Jiahe; Yu, Xinbo; Chen, Jiaqi; Wu, Zihua; He, Qian; Zhang, Yan; Song, Weijiang; Luo, Jing; Tao, Qingwen (Frontiers in Immunology, 2023)
Background Autophagy in osteoarthritis (OA) has become an active area of research with substantial value and potential. Nevertheless, few bibliometric studies have systematically analyzed the available research in the field. The main goal of this study was to map the available literature on the role of autophagy in OA and identify global research hotspots and trends. Methods The Web of Science Core Collection and Scopus databases were interrogated for studies of autophagy in OA published between 2004 and 2022. Microsoft Excel, VOSviewer and CiteSpace software were used to analyze and visualize the number of publications and associated citations, and reveal global research hotspots and trends in the autophagy in OA field. Results 732 outputs published by 329 institutions from 55 countries/regions were included in this study. From 2004 to 2022, the number of publications increased. China produced the most publications (n=456), prior to the USA (n=115), South Korea (n=33), and Japan (n=27). Scripps Research Institute (n=26) was the most productive institution. Martin Lotz (n=30) was the highest output author, while Caramés B (n=302) was the highest output author. Osteoarthritis and Cartilage was the most prolific and most co-cited journal. Currently, the autophagy in OA research hotspots include chondrocyte, transforming growth factor beta 1 (TGF-β1), inflammatory response, stress, and mitophagy. The emerging research trends in this field are AMPK, macrophage, senescence, apoptosis, tougu xiaotong capsule (TXC), green tea extract, rapamycin, and dexamethasone. Novel drugs targeting specific molecule such as TGF-β and AMPK have shown therapeutic potential but are still in the preclinical stage of development. Conclusions Research on the role of autophagy in OA is flourishing. Martin Lotz, Beatriz Caramés, and Osteoarthritis and Cartilage have made outstanding contributions to the field. Prior studies of OA autophagy mainly focused on mechanisms underlying OA and autophagy, including AMPK, macrophages, TGF-β1, inflammatory response, stress, and mitophagy. Emerging research trends, however, are centered around the relationship between autophagy, apoptosis, and senescence, as well as drug candidates such as TXC and green tea extract. The development of new targeted drugs that enhance or restore autophagic activity is a promising strategy for the treatment of OA.